Análise temporal do processo de ocupação dos vazios urbanos no município de São Carlos, SP : sob a ótica de uma cidade compacta - Barbosa, Yanayne Benetti (2018)
In this work, the mapping and analysis of the urban voids of São Carlos (SP), through GIS, showed the spatial dynamics through the valorization and or depreciation that urban areas present. The objective of this study was to analyze the the urban voids in different urban areas (established by the Plano Director) considering the years 2004 and 2014, in the municipality of São Carlos, SP. As a result, we highlight the detailed characterization of the historical series of land value in the urban voids and surroundings in the last twenty years. In addition, it is proposed a scenario that made it possible to simulate occupation that resulted in almost 40 thousand inhabitants in urban voids, maintaining the profile of occupancy and densification in urban zoning. Inside the new limit and rules of the 2016 Plano Diretor, the occupation of urban voids may promote, in addition to the occupation, a greater density, without need to increase the urban perimeter to fulfill the social function of the use of urban land, thus reducing the costs of deploying new urban infrastructure